2019
DOI: 10.1371/journal.pone.0214224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence estimation of Italian ovine cystic echinococcosis in slaughterhouses: A retrospective Bayesian data analysis, 2010–2015

Abstract: Cystic echinococcosis (CE) is a complex zoonosis with domestic and sylvatic life-cycles, involving different intermediate and definitive host species. Many previous studies have highlighted the lack of a surveillance system for CE, its persistence in Italy, and endemicity in several Italian regions. Because of the absence of a uniform surveillance program for both humans and animals, disease occurrence is widely underestimated. This study aimed to estimate the prevalence of ovine CE in Italy. Survey data on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
12
1
1
Order By: Relevance
“…In this way, the generalisability of the results can be ensured as much as possible. Furthermore, the association between CE and ISTAT territorial indicators for development policies has been successfully studied by Loi et al in 2019 [35], providing interesting results and underling the need of in deep studies. Data on the sex and age of the farmers were collected using the fiscal code downloaded by BDN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the generalisability of the results can be ensured as much as possible. Furthermore, the association between CE and ISTAT territorial indicators for development policies has been successfully studied by Loi et al in 2019 [35], providing interesting results and underling the need of in deep studies. Data on the sex and age of the farmers were collected using the fiscal code downloaded by BDN.…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis has subsequently studied in-depth by numerous studies [6] [7] [31] [32]. Furthermore, the spread of CE in association with social factors has also been studied in Sardinia, first by Brundu et al in 2014 [33] and subsequently by Piseddu et al in 2017 [34] and Loi et al in 2019 [35]. Recently, following the succession of numerous seasonal epidemics of bluetongue (BT) in Sardinia, the role of social factors and farm management has been studied extensively, demonstrating the importance of good management practices in disease prevention and relaying information about risk factors to the farmers [36] [37].…”
Section: Introductionmentioning
confidence: 99%
“…The data on the prevalence of CE in some Italian regions are scarce. In Basilicata prevalence ranging between 5-28% were reported in sheep from 1996 to 2002 [20] and of 12% from 2010 to 2015 [9]. No previous data were available for goats.…”
Section: Discussionmentioning
confidence: 99%
“…Deplazes et al [5] showed a heterogeneous geographic distribution in the European Mediterranean area with prevalence values < 0.1% in the coastal regions of France and Spain, reaching values > 50.0% in Italy, with a higher prevalence in the southern (Basilicata and Campania regions) and insular (Sardinia and Sicily) part of the country [8,9,10]. However, the reported prevalence of CE in livestock is widely underestimated, because the surveillance system based on reports recorded at slaughterhouses is still inefficient [9,11]. In addition, the data of surveillance systems are usually obtained for wide geographic areas that assume a homogeneous prevalence [12].…”
mentioning
confidence: 99%
“…Deplazes et al [ 5 ] showed a heterogeneous geographic distribution in the European Mediterranean area, with prevalence values < 0.1% in the coastal regions of France and Spain, reaching > 50.0% in Italy, with a higher prevalence in the southern (Basilicata and Campania regions) and insular (Sardinia and Sicily) part of the country [ 8 10 ]. However, the reported prevalence of CE in livestock is widely underestimated, because the surveillance system based on reports recorded at slaughterhouses is still inefficient [ 9 , 11 ]. In addition, surveillance system data are usually obtained for wide geographic areas without considering that the prevalence of CE can differ widely in different points of the same area [ 12 ].…”
Section: Introductionmentioning
confidence: 99%